Rates of Reaction of Atomic Oxygen III. Spiropentane, Cyclopentane, Cyclohexane, and Cycloheptane - Huie, Robert E. (J Res Natl Bur Stand A Phys Chem, 1972)
Rate constants have been measured from 307 to 652 K for the reactions of atomic oxygen (O(3)P) with spiropentane, cyclopentane, cyclohexane, and cycloheptane. The derived Arrhenius parameters are k(sp − C(5)H(8)) = 10(13.60±0.10) exp[(−2890 ± 100)/T], k(cy − C(5)H(10)) = 10(14.10±0.09) exp[(−2210 ± 100)/T], k(cy − C(6)H(12)) = 10(14.35±0.09) exp[(−2350 ± 100)/T], and (cy − C(7)H(14)) = 10(14.46±0.13) exp[(−2230 ± 100)/T] all in units of cm(3) mol(−1) s(−1).